Thrombotic Thrombocytopenic Purpura Associated with the Acquired Immune Deficiency Syndrome - Anand Kumar; Jean Wang; David Sutton; Eric J Bow (Canadian Journal of Infectious Diseases)
A bisexual male presented with acute thrombotic thrombocytopenic purpura (TTP) in association with established acquired immune deficiency syndrome. The patient had classic clinical and laboratory findings of TTP and responded well to plasmapheresis therapy. Previously reported cases of TTP in association with human immunodeficiency virus (HIV) infection are briefly reviewed. Basic concepts in the pathogenesis of TTP are examined in reference to HIV infection.